Female directors and corporate cash holdings: monitoring vs executive roles. Issue 2 (4th December 2019) - Cambrea, Domenico Rocco; Tenuta, Paolo; Vastola, Vincenzo
Abstract : Purpose: The purpose of this paper is to investigate the impact of gender diversity on corporate cash holdings by scrutinizing different positions covered by female board directors. Design/methodology/approach: The paper examines a sample of Italian listed companies between 2006 and 2015. Fixed-effects regressions are employed as the base empirical methodology. In addition, because the link between corporate governance variables and cash may suffer from endogeneity issues, the study employs several tests to control for this potential problem. Findings: The empirical findings demonstrate that the relationship between gender diversity and cash holdings depends on the role of female directors on the boards. Specifically, the evidence shows that women in monitoring functions, ruled by independent directors and female chairs, led to a decrease in cash reserves. Conversely, companies managed by female CEOs have larger cash holdings. Research limitations/implications: The paper refers to Italian listed companies only and does not analyze whether and how the financial crisis has affected the link between female directors and cash reserves. Practical implications: The study provides insights for the diverse effects of female directors on cash management decision and contributes to the debate on gender diversity capabilities for improving firm financial flexibility. Originality/value: This paper is the first empirical study to attempt to disentangle the effect of gender diversity on cash holdings. It sheds light on the consequences of appointing female directors on cash policies and explores the Italian context after the introduction of the gender quotas law.